A relação sofrimento/prazer dos empresários do setor de seguros no exercício da sua atividade profissional - Souto, Claúdia Helena Oliveira de (2017)
This work aims at understanding the relation between suffering and pleasure of broker businessmen occur, considering the elements that they encounter in their daily work routine. This purpose is developed in specific objectives that focus on understanding how these entrepreneurs organize themselves in their work activity in order to face the problems related to their profession, in the following plans: their relation with the collective of profession and the systems of defence collectively established; the resources that they use to remain in the normal field and the moment that these resources reveal insufficiency; the forms of recognition or the lack of it, subordinates, clients and suppliers and the level of dynamic balance that the participant can achieve in relation to the activities demanded by the company and his private life, including the family. Ten insurance businessmen from the city of João Pessoa / PB participated in this study, who met the requirements of having at least five years of experience in business activity, being responsible for the administration of their companies and being Official Insurance Brokers, qualified by the Superintendence of Private Insurance (SUSEP). The theoretical framework that supported this study was the Psychodynamics of Work. Regarding the method, this research is characterized by being a field study, of a qualitative nature, comprising the following instruments: socio-demographic questionnaire, with the interviewee's professional data and a semi-structured interview. The analysis of the data was developed through the analysis of content snippet by themes. It was identified that despite working in solitude, the entrepreneur, as well as his employee, needs a collective environment to count on, even if it is a contestant; most of them have diseases that have been caused or aggravated by their work and that all of them have had stresses resulting from this activity. It was also verified that, in the struggle for normality, entrepreneurs use strategies to get out of suffering problems; the recognition of their work has fundamental importance for the performance of their activity and that in the company / family relationship there is no classic separation between work and non-work, since the company not only interferes in the family, but is part of it.